From autocracy to oligarchy : elite adjustment and authoritarian legacies in the Jokowi’s administration - Taufik,; Muhamad M. N. Nadzri,; Jamaie Haji Hamil, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Democratic breakthrough in Indonesia in the late 1990s was made possible through the dynamic interactions between the civil society organisations (CSOs) and its ruling elites. Although some of the former ruling elites were affected by the political transformation, others have evolved and survived as ‘authoritarian diasporas,’ In fact, the former ruling party, Golkar, also survived the change and is considered one of the ‘authoritarian successors parties.’ Based on these two conceptions developed by James Loxton and elite adjustment by Panji Anugrah Permana, this article explores the resilience of authoritarian legacies in post-Reformasi Indonesia, particularly among the authoritarian diaspora and its influences on Indonesia’s democratisation, particularly during the Jokowi years. By examining the three main sectors among the former authoritarian elites in politics, businesses, and the military, this article makes a case for democratic backsliding in Indonesia under the Jokowi administration due to the resurgence and the roles played by the former authoritarian elites in re-capturing politics and political change from the CSOs. The analysis in this article is based on a field study and library research.